ENDOSCOPE-ASSISTED POSTAURICULAR SURGERY FOR BENIGN PAROTID TUMORS (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of endoscope-assisted postauricular surgery for benign parotid tumors.Methods: This was a literature review study. Search PubMed and ScienceDirect to identify relevant articles, followed by screening, analysis, and synthesis of data to assess the application of endoscope-assisted postauricular parotidectomy for benign tumors.Conduct a comprehensive review of the thesis. Utilize PubMed and Science Direct databases for the search.Results: A total of 12 studies published between 2007 and 2026 were included, comprising 7 retrospective and 5 prospective studies. Endoscope-assisted postauricular surgery achieved complete tumor removal with a low recurrence rate. Compared with the conventional open approach, the endoscope-assisted group demonstrated shorter incision length, reduced intraoperative blood loss, and lower or comparable postoperative complication rates, along with superior cosmetic outcomes.Conclusion: Endoscope-assisted postauricular surgery for benign parotid tumors is a feasible, safe, and effective technique. It provides a minimally invasive alternative that improves cosmetic outcomes and preserves function in appropriately selected patients.
Keywords: Postauricular parotidectomy, endoscope-assisted.